Consultas planteadas al ICAC - Gálvez Linares, Miguel Ángel; Romano Aparicio, Javier (Revista de Contabilidad y Tributación. CEF, 2003)
BOICAC núm. 48, 12-2001. Consulta 4 BOICAC núm. 39, 09-1999. Consulta 3